Ratios, proportions, and mixtures of chlorophylls: Corrections to spectrophotometric methods and an approach to diagnosis. (16th July 2015) - Henderson, I. M.
Abstract: Ratios of absorbances at two wavelengths have been used to quantify mixtures of photosynthetic pigments such as chlorophylls, phaeophytins and bacteriochlorophylls, however published methods have either specified an incorrect relationship between the absorbance ratio and the mixture, or only presented the relationship graphically. The correct relationship is established along with correct forms for equations to calculate pigment densities from absorbance ratios. The limitations of simple ratios and a diagnostic approach using difference spectra are illustrated with an example involving mixtures of oxygenic and anoxygenic phytoplankton communities in a stratified lake.